On the Family Origins of Human Capital Formation: Evidence from Donor Children - Petter Lundborg; Erik Plug; Astrid Würtz Rasmussen (Institute of Labor Economics (IZA), 2021)
We introduce a novel strategy to study the intergenerational transmission of human capital, net of genetic skill transfers. For this purpose, we use unique data on children conceived through sperm and egg donation in IVF treatments in Denmark. Because the assignment of donors is not selective, the intergenerational human capital estimates allow for a causal nurture interpretation. Once we take account of genes, we find that only the education of mothers matters: the association between mother's education and child test scores is significant and large, whereas the association between father's education and child test scores is insignificant and practically zero.
Keywords: I24; J62; 330; intergenerational mobility; human capital; donor children